2 - Musical Hybridity in Flux: Representing Race, Colonial Policy, and Modernity in French North Africa, 1860s-1930s - Jann Pasler, (Afrika Zamani, 2022)
Colonialism posed the challenge of coexistence amid almost insurmountable differences. Music had long been considered an audible representation of these differences, the performance of intelligence, character, and even soul. French colonial policies, ranging from assimilation to association, too impacted how music was understood and what function it could play. Under assimilationist colonialism, some French hoped that appropriating foreign ideas and the hybridities that resulted could lead to innovation. After 1900, however, attention turned from exploiting cultural differences to wanting to preserve them. Here I examine three genres in which European and African music were brought into hybrid relationships: piano/vocal transcriptions of African melodies by Salvador Daniel, Jules Rouanet and Edmund Yafil in Algiers, Antoine Laffage and Baron Rudolph d’Erlanger in Tunis, and Alexis Chottin in Morocco; orchestral music that incorporates African melodies, rhythms, and timbres by Camille Saint-Saëns; and marches by Africans as well as French composers, with narratives of not only triumph, but also accommodation and resistance. This music and the ideologies behind its hybridities encourage us to reflect on issues at the heart of the colonial process.